PENGARUH PERTIMBANGAN ETIS, PERILAKU MACHIAVELIAN, DAN GENDER DALAM PEMBUATAN KEPUTUSAN ETIS MAHASISWA S1 AKUNTANSI - Suliani, Metta; Marsono, Marsono (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2010)
This research had purposed to test and to know how big the impact of ethical reasoning,Machiavellian behaviour, and the impact of gender to ethical decision making. This research alsopurposed to found if there were any different impact of ethical reasoning, Machiavellian behaviourand gender between the group of accounting students in Satya Wacana Christian University andAtma Jaya Catholic University. This research used Purposive Sampling to choosed the sample.Sample of this research are 93 accounting students in Satya Wacana Cristian University and 97students in Atma Jaya Catholic University that have passed the Auditing I and Auditing II lessons(the name of the lessons depends on the curriculum of the university). Number of the samplewas obtained by the Slovin formula. The result indicated that on both sample, Machiavellianbehaviour had impacted the ethical decision making, whether on first or second condition. Butthe ethical reasoning and gender did not have impact on ethical decision making. This reseachalso indicated that there were no result differences between the group of accounting students inSatya Wacana Christian University and Atma Jaya Catholic University.